PENGARUH KREDIT USAHA RAKYAT TERHADAP PROFITABILITAS UMKM DI KABUPATEN PARIGI MOUTONG - I Kadek Adi Aribawo; Muhammad Faisal; Husnah Husnah (Universitas Tadulako, 2019)
Research objectives, (1) To analyze the impact of entrepreneurship quality on the effectiveness of KUR in increasing profitability (2) Analyzing the impact of business scale on the effectiveness of KUR in increasing profitability. (3) Analyzing the profitability level of UMKM with Micro KUR. (4) Analyze the profitability level of UMKM with Retail KUR. (5) Analyze the level of profitability of UMKM simultaneously with Micro KUR and Retail KUR. The results of the study, (1) The absence of a relationship between profitability and the experience of entrepreneurs managing small businesses, because experience does not improve the entrepreneurial innovation competence. (2) Hasi refers to the consistency of the relationship between size or business scale and profitability. (3) The significance value of 0.903> 0.05 can be concluded that Micro KUR does not affect the profitability of UMKM in Parigi Moutong Regency. (4) It is known that the significance value is 0.039 <0.05 so that it is concluded that Retail KUR influences the profitability of UMKM in Parigi Moutong Regency. (5) Given the significance value of 0.106> 0.05 it can be concluded that the KUR Fund does not affect the profitability of UMKM in Parigi Moutong Regency. Tujuan penelitian, (1) Menganlisis dampak kualitas enterpreneur terhadap efektivitas KUR dalam meningkatkan profitabilitas.(2) Menganlisis dampak skala usaha terhadap efektivitas KUR dalam meningkatkan profitabilitas. (3) Menganalisis tingkat profitabilitas UMKM dengan KUR Mikro. (4) Menganalisis tingkat profitabilitas UMKM dengan KUR Ritel.(5) Menganalisis tingkat profitabilitas UMKM secara simultan dengan KUR Mikro dan KUR Ritel. Hasil penelitian, (1) Tidak adanya hubungan antara profitabilitas dengan pengalaman enterpreneur mengelola usaha kecil, karena pengalaman tidak meningkatkan kompetensi inovasi seorang enterpreneur. (2) Hasi memenujukan konsistensi hubungan antara size atau skala usaha dengan profitabilitas. (3) Diketahui nilai signifikansi sebesar 0,903 > 0,05 dapat disimpulkan bahwa KUR Mikro tidak berpengaruh terhadap Profitabilitas UMKM di Kabupaten Parigi Moutong. (4) Diketahui nilai signifikansi sebesar 0,039 < 0,05 sehinga disimpulkan bahwa KUR Ritel berpengaruh terhadap Profitabilitas UMKM di Kabupaten Parigi Moutong. (5) Diketahui nilai signifikansi sebesar 0,106 > 0,05 dapat disimpulkan bahwa Dana KUR tidak berpengaruh terhadap Profitabilitas UMKM di Kabupaten Parigi Moutong.